Solution (a):
~Let's change 9.9² to 10² since we have to estimate.~
We know that:
- 10² = 100
- Given expression: 9.9² × 1.79
Solving the expression:
- 9.9² × 1.79
- => 10² × 1.79
- => 100 × 1.79
- => 179
The estimated value of 9.9² × 1.79 is 179.
Solution (b):
~Let's change √97.5 to √100 and 1.96 to 2 since we have to estimate.~
We know that:
- √100 = 10
- Given expression: √97.5 ÷ 1.96
Solving the expression:
- √97.5 ÷ 1.96
- => √100 ÷ 2
- => 10 ÷ 2
- => 5
The estimated value of √97.5 ÷ 1.96 is 5.